2019
DOI: 10.21106/ijma.337
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Overweight and Obesity Among Children in the United States

Abstract: Background: Childhood obesity is one of the foremost threats to population health in the United States (U.S.) leading to the emergence of co-morbidities and increased healthcare cost. We explore the influence of selected social determinants of health (SDOH) on overweight and obesity among U.S. children. Methods: We utilized the National Survey of Children’s Health (NSCH) 2016-17 dataset for this analysis. Overweight was defined as Body Mass Index (BMI) ? 85 th to<95 th , while obesity was defined as B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 27 publications
(56 reference statements)
2
29
0
Order By: Relevance
“…Thus, we observed that being a girl or boy did not predict the likelihood of having excess weight/obesity, a finding that is consistent with some previous studies conducted [42,43]. However, contrary to our results, some other studies either reported differences in obesity prevalence between the sexes [17,21,44] or found girls to be at increased risk for childhood obesity [39]. In the case of %BF, we found a greater number of girls with higher adiposity than boys.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, we observed that being a girl or boy did not predict the likelihood of having excess weight/obesity, a finding that is consistent with some previous studies conducted [42,43]. However, contrary to our results, some other studies either reported differences in obesity prevalence between the sexes [17,21,44] or found girls to be at increased risk for childhood obesity [39]. In the case of %BF, we found a greater number of girls with higher adiposity than boys.…”
Section: Discussionsupporting
confidence: 83%
“…Hispanic youth are disproportionately impacted by SDoH that have been associated with increased rates of obesity and obesity-related diseases [ 61 , 62 , 63 ]. Thus, intervention strategies should consider the SDoH that may limit disease prevention opportunities and health behaviors that may be leveraged or addressed within interventions to increase engagement and adherence [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intricate determinants for overweight and obesity are discussed in many studies (6)(7)(8)(9)(10)(11)(12)(13). Biologically, overweight and obesity are caused by an imbalance between energy intake and energy expenditure (14).…”
Section: Introductionmentioning
confidence: 99%